An improved electrophoretic method for the determination of serum milk protein variants in Gyr-Holstein cows. - Ramos, P. R. [UNESP]; Urtado, S. L. [UNESP]; Almeida, M. R. [UNESP]; Bortolozzi, J. [UNESP]; Silva, E. T. [UNESP] (My University, 1992)
Milk serum proteins such as alpha-lactalbumin (ALA) and beta-lactoglobulin (BLG) present biochemical polymorphism which is under the control of codominant autosomal alleles. In the present report, we propose modifications of traditional electrophoretic techniques such as increasing the running gel concentration from 5 to 10% and the addition of 5 M urea to the stacking gel, which permitted the detection of two variants (A and B) at the ALA and BLG loci. About 8 microliters of milk serum (6 mg/ml protein) and 10 microliters of total fresh milk were applied. Bovine serum albumin (BSA) and immunolactoglobulins (ILG) could also be discriminated. Total fresh milk was as useful as the purified serum milk proteins for the discrimination of ALA and BLG serum milk protein polymorphism by alkaline vertical slab polyacrylamide gel electrophoresis. However, BSA and ILG ran with caseins, which prevented their characterization in this system.